User experience in information system platforms: A study on learning styles and academic challenges - Chong chong Yang; Soon Singh Bikar Singh (Innovative Information Science and Technology Research Group, 2024)
Understanding student academic struggles and improving the use of information system platforms are essential for enhancing higher education. This study aims to examine how course management and student learning patterns affect higher education, particularly in the context of escalating academic challenges and competition in China. Using a quantitative-method approach, this research analyzes students' independent, cooperative, and inquiry learning styles to explore the relationship between course settings, student learning patterns, and academic difficulties using a 400 sample size. This study indicated that inquiry-based learning fosters critical thinking and deeper topic engagement but also provides academic challenges that can delay student progress. Inquiry-based learners struggle with time management and hard topics without institutional guidance, therefore they may not be right for all college students. The study found that current information system platforms encourage traditional or autonomous learning, which may preclude collaborative or inquiry-based learners. These platforms lack resources and adaptability to meet all learners' needs, which may harm academic success. Higher education benefits from supporting varied learning styles. To help diverse student groups overcome academic problems, information system platforms should contain more adaptive and specialist educational technologies. The study offers educators practical advice on creating a more inclusive curriculum that satisfies diverse learning needs by studying course administration and user experience. Real-time feedback and flexible modules may alleviate academic stress for inquiry-based learners. The findings also suggest that governments should promote more flexible educational technologies that can accommodate varied teaching techniques and student preferences.